Awareness Regarding Polycystic Ovarian Syndrome Among Adolescent Girls (International Journal of Scientific Research in Science and Technology, 2024)
The present study was conducted on “Awareness regarding polycystic ovarian syndrome among adolescent girls” with the objectives to assess awareness level regarding polycystic ovarian syndrome among adolescent girls, and to find out the problems faced by polycystic ovarian syndrome girls. The study was conducted on 100 students of B.B.A, B.A and B.des 1st year from Banasthali Vidyapith. Self-constructed questionnaire tool was used for this study. For analyzing the data following statistical measures were used such as mean, frequency, percentage, and One-Way ANOVA. The result of the study revealed that there is no significant difference in awareness level between B.A, B.B.A and B.des 1st year students. 50% of students come under the below-average category, 30% of students come under the average category, and 20% of students come under the above-average category of awareness about polycystic ovarian syndrome. All students had a low level of awareness regarding polycystic ovarian syndrome so they needed an awareness program to increase knowledge about polycystic ovarian syndrome.
Keywords: Awareness; Infertility; Menstruation; Ovary; Polycystic Ovarian Syndrome